Policy and reality : the teaching of oral communication by Japanese teachers of English in public junior high schools in Kurashiki City, Japan : a thesis presented in the fulfilment of the requirements for the degree of Master of Arts in Second Language Teaching at Massey University, Palmerston North, New Zealand - Rapley, Douglas James (Massey University, 2008)
In 2003 the Ministry of Education, Culture, Sports, Science and Technology (MEXT) unveiled their new junior high school (JHS) English as a Foreign Language (EFL) policy, which focused strongly on oral communication. Although there is evidence of policy noncompliance in schools until now there has been no English language research on the attitudes or practices of Japanese teachers of English (JTEs), or the views of the students, and their parents in regards to teaching/learning English speaking skills. The research, based on JHSs in a mid-sized Japanese city (pop. 475,000 approx.), focused predominantly on JTEs, but also included students, and their parents. Focus group sessions, questionnaires, and one-on-one interviews were used to collect data. The study reveals that learning English speaking skills is considered important, but passing the senior high school (SHS) entrance examination is the main concern and so, test impact from the SHS entrance examination exerts the greatest pressure on JHS JTEs. The JTEs also perceive themselves as facing other issues such as student motivation, JTE speaking proficiency, and large class sizes. Another finding is that JTEs appear to receive inadequate training– pre- and inservice– resulting in issues, such as a reliance on traditional methods (yakudoku), which are not in accordance with MEXT’s intentions, and JTE proficiency test achievement levels lower than those desired by MEXT. As a result of these issues gaps exist between MEXT JHS EFL policies and actual teaching practices, and have unfortunately led to a situation where JTEs believe that MEXT does not care about or understand the teaching environment. The study concludes that implementation of MEXT’s policy require a better match between the SHS entrance examination and JHS EFL policy, a decrease in class sizes, and JTEs receiving more adequate training. A more positive relationship between MEXT and JTEs would result from these two groups working collaboratively when designing JHS EFL policies and could better achieve a match between the SHS entrance examination and JHS EFL policy.
Keywords: English language teaching; Spoken English; Policy; Japan; Fields of Research::330000 Education::330200 Curriculum Studies